Enhancing learning: impact of virtual reality simulations on academic performance and perception in biological sciences in psychology students - Carrasco, Carlos M.; Cabezas, Felipe; Contreras, Felipe A.; Aracena, Claudia; Laroze, Liza; Figueroa, Pablo (Frontiers in Education, 2025)
The growing number of students in higher education has raised challenges in inclusion and equity due to the diversity of students’ backgrounds and entry-level skills. Educational institutions must adapt teaching-learning strategies to ensure the achievement of learning outcomes. In this context, Information and Communication Technologies (ICTs), combined with gamification, offer tools like Labster™, which enable interactive scientific simulations and promote active learning. This study used a quasi-experimental design with self-selected participation to evaluate the impact of Labster in a “Biological Foundations of Psychology” course across nine nationwide sections. The sample consisted of 315 first-year Psychology students, 237 in the experimental group and 78 in the control group. Given the non-normal distribution of academic data (Shapiro-Wilk test, p < 0.05), non-parametric tests were applied. A Kruskal-Wallis test on learnng gain (final minus initial grade) showed that students using Labster achieved significantly greater academic improvement than the control group (H = 12.347, p = 0.00004). A multiple linear regression, controlling for baseline performance (cat_1, ej_1, ta_1), confirmed that participation in the intervention predicted higher final grades (β = 0.3891, p = 0.0053; adjusted R2 = 0.216). No significant differences were found between the two types of simulations used (Kruskal-Wallis, p = 0.2814). A perception survey was administered to 237 Labster users, of whom 87 responded (response rate: 36.7%). The results revealed positive evaluations regarding usability, academic relevance, and motivational impact. In summary, Labster-based virtual simulations enhance academic performance and individual progress in scientific learning among psychology students, especially in diverse and non-science-oriented populations.